A Meta‐Analysis of the Utility of C‐Reactive Protein, Erythrocyte Sedimentation Rate, Fecal Calprotectin, and Fecal Lactoferrin to Exclude Inflammatory Bowel Disease in Adults With IBS. (March 2015) - Menees, Stacy B; Powell, Corey; Kurlander, Jacob; Goel, Akash; Chey, William D
Abstract : Objectives: Irritable bowel syndrome (IBS) is viewed as a diagnosis of exclusion by most providers. The aim of our study was to perform a systematic review and meta‐analysis to evaluate the utility of C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR), fecal calprotectin, and fecal lactoferrin to distinguish between patients with IBS and inflammatory bowel disease (IBD) and healthy controls (HCs). Methods: A systematic online database search was performed. Included studies were prospective, adult, diagnostic cohort studies with any of the four tests. The means and s.d. values of biomarker logarithms were estimated based on studies that gave medians and either confidence intervals for the median, interquartile ranges, or ranges. We used a Naive Bayes approach to estimate the probability of being a HC, having IBS, or having IBD based on the biomarker values. Results: Systematic review identified 1, 252 citations. After cross‐referencing medical subject headings, detailed evaluation identified 140 potentially relevant journal articles/abstracts for CRP, ESR, calprotectin, and lactoferrin of which 4, 4, 8, and 2 fulfilled our inclusion criteria, respectively. None of the biomarkers reliably distinguished between IBS and healthy controls. At a CRP level of ≤0.5 or calprotectin level of ≤40 μg/g, there was a ≤1% probability of having IBD. Individual analysis of ESR and lactoferrin had little clinical utility. Conclusion: CRP and calprotectin of ≤0.5 or 40, respectively, essentially excludes IBD in patients with IBS symptoms. The addition of CRP and calprotectin to symptom‐based criteria may improve the confident diagnosis of IBS.